An Analysis Of The Conflict Faced By The Main Characters In Laskar Pelangi Film - Anggraini, Melia; Pradana, Ami; Rahman Putra, Aziiz (CV. Multi Kreasi Media, 2024)
This study analyzes the conflicts faced by the main characters in the film